2021
DOI: 10.3390/molecules26206173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship among Biogenic Amines, Nitrite and Microbial Diversity in Fermented Mustard

Abstract: Biogenic amines (BAs) and nitrites are both considered harmful compounds for customer health, and are closely correlated with the microorganisms in fermented mustard (FM). In this study, BAs and nitrite contents in fifteen FM samples from different brands were analyzed. The concentrations of cadaverine in one sample and of histamine in one sample were above the toxic level. Moreover, five FM samples contained a high level of nitrite, exceeding the maximum residue limit (20 mg/kg) suggested by the National Food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Total biogenic amines and nitrites are generally selected as negative indicators for fermented foods, even though they are relatively scarce in fermented vegetables and fruits ( Yu et al, 2021 ). Levels of total biogenic amines in the fermented cucumbers pickling juices were significantly ( P < 0.05) increased through the 16-days fermentation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Total biogenic amines and nitrites are generally selected as negative indicators for fermented foods, even though they are relatively scarce in fermented vegetables and fruits ( Yu et al, 2021 ). Levels of total biogenic amines in the fermented cucumbers pickling juices were significantly ( P < 0.05) increased through the 16-days fermentation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fermented mustard is a traditional product of vegetable fermentation that is produced by spontaneous fermentation with microorganisms coming from raw materials (Yu et al, 2021). During fermentation, BAs are generally produced by microorganisms through enzymatic decarboxylation of amino acids (Park et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Biogenic amines were significantly affected by complex microbial communities. Yu et al (2021) investigated the correlations between microbial communities and BAs by 16S rRNA metagenomics, which showed that tryptamine positively correlates with Lactobacillus and Pseudomonas, while cadaverine is positively correlated with Leuconostoc. Nevertheless, the genes responsible for encoding the amino acid decarboxylase inside foods processed by fermentation were unable to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli from several naturally fermented pickles can produce putrescine (PUT), cadaverine (CAD), and histamine (HIS) [ 106 ]. CAD and nitrite are associated with Leuconostoc , while Lactobacillus and Pseudomonas are associated with tyramine (TYR) [ 107 ]. Lactobacillus brevis primarily produces TYR [ 108 ].…”
Section: Safety Problems In Fermented Vegetables and Current Solutionsmentioning
confidence: 99%
“…Various fermented foods have been discovered that contain bacteria capable of degrading biogenic amines [ 112 ], and the strains which are related to fermented vegetables are listed in Table 2 . Lactobacillus plantarum [ 113 ], L. plantarum GZ-2, L. brevis SC-2 [ 107 ], Levilactobacillus brevis PK08, Lactiplantibacillus pentosus PK05, Leuconostoc mesenteroides YM20, L. plantarum KD15, and Latilactobacillus sakei YM21 [ 114 ] have all been identified as strains that do not produce or degrade biogenic amines. Different strains can degrade biogenic amines at varying rates [ 115 ].…”
Section: Safety Problems In Fermented Vegetables and Current Solutionsmentioning
confidence: 99%